Analysis of Occupational Health and Safety (OHS) Implementation in the New Building Construction at UPT Railway Resort 8.10 Sidotopo - Aldianto, Muhammad Affan; Yudhana, Amarin; Sodik, Mohammad Ali; Sari, Reny Mareta (Universitas STRADA Indonesia, 2025)
The implementation of Occupational Health and Safety (OHS) is a crucial aspect of construction projects to protect worker safety and improve work efficiency. Although regulations such as the Ministry of Public Works and Housing Regulation (Permen PUPR) No. 10 of 2021 have been enforced at the UPT Railway Resort 8.10 Sidotopo, challenges remain in their practical application on site. This research employs a descriptive qualitative approach through direct observation and in-depth interviews with workers, foremen, and OHS officers at the project location. The analysis compares field conditions against applicable OHS regulatory standards and relevant theoretical literature. Results indicate that OHS implementation in this project is administratively compliant, including daily briefings, routine inspections, and the provision of personal protective equipment (PPE). However, inconsistencies were found in the use of PPE by workers, especially under hot working conditions and high schedule pressure. Factors such as leadership, facilities, training, as well as psychosocial aspects and safety culture influence the level of worker compliance. A comprehensive approach is needed by strengthening the safety culture, providing more interactive training, and integrating the Prevention through Design principle to mitigate work risks from the planning stage. Active worker participation and adaptive risk management are also key to creating a safe and sustainable work environment.